METHOD DEVELOPMENT FOR QUANTIFICATION OF LORATIDINE AND ALVERINE CITRATE BY VISIBLE SPECTROPHOTOMETRY (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
The present work describes on two colorimetric methods based on charge transfer complex reaction of loratidine (LRT) and alverine citrate (ALV) with chloranilic acid in chloroform. The methods were developed on Perkin Elmer LAMBDA 25 UV –VIS spectrophotometer with 1cm quartz cells. The methods were optimised to achieve maximum colour intensity and validated for reliability. The coloured complexes showed maximum absorbance at 538 nm for LRT and 540 nm for ALV. The absorbances were found to increase linearly with increase in concentration which was emphasised by the calculated regression coefficients (0.9998-0.9999). Linearity of standard plot was in the order of 100-700 and 80-560µg/ml for LRT and ALV, respectively. The molar absorptivity, sandells sensitivity, LOD, LOQ and other validation parameters have been assessed extensively and all the parameters seem to comply with the acceptance criteria. The proposed methods were proved to be more accurate, simple, precise and rapid by statistical validation, recovery studies and could be appropriate to employ in regular laboratory analysis.